Philippa Fisher and the fairy godsister - Kessler, Liz (Kessler, Liz. Philippa Fisher, 2015)
Philippa Fisher would like nothing more than a fairy godmother to grand her wishes. Instead, she gets Daisy, her same-age godsister. But Daisy not too fond of humans, and Philippa's wishes keep everything worse. Will they come together to fix the mess thay've created before it's too late?